2000
DOI: 10.1111/j.1708-8208.2000.tb00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonsubmerged Implants in the Treatment of the Edentulous Upper Jaw: A Prospective Clinical and Radiographic Study of ITI Implants—Results after 1 Year

Abstract: The ITI screw implants, used in the edentulous upper jaw, had a survival rate of 92.8%. Mean bone loss between loading and the 1-year examination was 0.1 mm. Some implants had a bone level indicating a significant bone loss before loading. Peri-implantitis was found at about 7.2% of the implants inserted and at 25% of the failing implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…In preclinical investigations, such extremely rough surface topography of the TPS surface presented improved osseointegration compared to the turned surfaces [56][57][58]. Unfortunately, the clinical trials seemed to present little or rather negative outcomes with progressive marginal bone loss [59][60][61][62][63][64][65][66], resulting in TPS-roughened implant surfaces falling from favor among implant manufacturers.…”
mentioning
confidence: 98%
“…In preclinical investigations, such extremely rough surface topography of the TPS surface presented improved osseointegration compared to the turned surfaces [56][57][58]. Unfortunately, the clinical trials seemed to present little or rather negative outcomes with progressive marginal bone loss [59][60][61][62][63][64][65][66], resulting in TPS-roughened implant surfaces falling from favor among implant manufacturers.…”
mentioning
confidence: 98%
“…18,19,21 On the other hand, divergent results have also been reported showing that there may be a greater risk of implant failure with the non-submerged technique. 22,28 Earlier clinical studies on non-submerged implant insertion evaluated implant success rates with this technique. 19,21,22,24 Most of these studies showed that there was a tendency towards greater implant loss with the non-submerged technique, 18,22,25 due to the possibility of epithelial down-growth or fibrous encapsulation resulting in failure of the implant to osseointegrate.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, literature data are quite unanimous in considering highly rough surfaces more attractive for plaque formation and more exposed to the occurrence of a perimplantitis process with consequent marginal bone resorption. [21][22][23][24][25][26] It is well known that both chemical and topographical surface characteristics may considerably affect the biological features of a substratum. Bacteria are very sensitive to any surface alteration, as well as to any external substance which they may come in contact, 35 but human cells and bacteria may respond differently to such modifications.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have showed that the use of such highly rough surfaces couples with higher bacterial plaque retention and marginal bone loss due to perimplantitis. [21][22][23][24][25][26] The purpose of the present study was to investigate if an additional treatment of TiN-coating of conventional titanium plasma sprayed implant surfaces could affect their properties in terms of topographic characteristics, affinity towards bone osteoprogenitors (human bone marrow mesenchymal stem cells), and susceptibility to bacterial colonization (Streptococcus pyogenes and Streptococcus sanguinis).…”
Section: Introductionmentioning
confidence: 99%